2022
DOI: 10.4081/ejh.2022.3391
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis resistance cooperates with cellular senescence in the overt stage of nonalcoholic fatty liver disease/nonalcoholic steatohepatitis

Abstract: Cellular senescence and ferroptosis are the two main, fine-tuned processes in tissue damage restraint; however, they can be overactivated in pathologies such as nonalcoholic fatty liver disease/nonalcoholic steatohepatitis (NAFLD/NASH), becoming dangerous stimuli. Senescence is characterized by a decline in cell division and an abnormal release of reactive oxygen species (ROS), and ferroptosis is represented by iron deposition associated with an excessive accumulation of ROS. ROS and cellular stress pathways a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Ghasemi et al discovered that iron overload decreases the activity of antioxidant enzymes in the liver, causing the liver to create a significant concentration of ROS and impairing liver function [ 36 ]. Vetuschi et al showed that iron overload could antagonize ferroptosis through negative feedback regulation of hepatic release of glutathione peroxidase 4 [ 37 ]. Through its potential to eliminate free radicals, melatonin exhibits its antioxidant actions and protects the liver from oxidative stress [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ghasemi et al discovered that iron overload decreases the activity of antioxidant enzymes in the liver, causing the liver to create a significant concentration of ROS and impairing liver function [ 36 ]. Vetuschi et al showed that iron overload could antagonize ferroptosis through negative feedback regulation of hepatic release of glutathione peroxidase 4 [ 37 ]. Through its potential to eliminate free radicals, melatonin exhibits its antioxidant actions and protects the liver from oxidative stress [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased HMGB1 is considered the hallmark of senescent astrocytes [ 69 ] and the HMGB1 signaling canonical pathway was activated by both PS particles. The SASP secretome, which results from excessive senescence, alerts the immune system to the onset of injury, coordinates the deletion of senescent cells and can contribute to increased cancer risk and age-related diseases [ 110 , 111 , 112 , 113 ]. Studies have shown that exposure to MPs/NPs leads to increased cellular senescence, as seen in rat lung tissue, zebrafish gills, and porcine coronary artery endothelial cells exposed to PS-MPs [ 114 , 115 , 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…PAs, as representative long‐chain non‐esterified SFAs, confer strong lipotoxic effects and can trigger several types of cell death. An in vitro experimental study has shown that PAs can induce ferroptosis and lipid deposition through the regulation of ferroptosis‐related factors (Vetuschi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05, **P < 0.01 as compared with BSA; # P < 0.05, ## P < 0.01 as compared with PA; + P < 0.05, ++ P < 0.01 as compared with PA + AS IV 80. converted to triglycerides, which then accumulate in cardiomyocytes and subsequently damage them, eventually leading to cell death (Hu et al, 2021). PAs are the most abundant saturated fatty acid (SFA) in the body, accounting for 25%-32% of the total serum FAs (Chu et al, 2019) through the regulation of ferroptosis-related factors (Vetuschi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%